t-test using STATA software - Fuad, Maher D. Fuad; Lye, Munn Sann; Ibrahim, Normala; Phang, Cheng Kar; Ismail, Siti Irma Fadhilah; Nasir Al-Zurfi, Balsam Mahdi (Universiti Sains Malaysia, 2015)
Students-t test is the most popular statistical test. The test compares two mean values to judge if they are different or not. For small data it is possible to conduct it using manual calculation – however that is not the case. Researchers would need to use statistical software and packages to conduct their analysis. This guide will help the junior researchers to conduct independent- and paired-t test using STATA software.